2016
DOI: 10.1097/sla.0000000000001902
|View full text |Cite
|
Sign up to set email alerts
|

Can CT-PET and Endoscopic Assessment Post-Neoadjuvant Chemoradiotherapy Predict Residual Disease in Esophageal Cancer?

Abstract: The prediction of pCR through CT-PET and endoscopy independently or combined is limited by low sensitivity and poor positive predictive value. Protocols to avoid surgery in patients with apparent complete clinical complete based on these criteria should be adopted with considerable caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…To implement non‐surgical treatment for advanced oesophageal cancer it is critical to accurately identify pCR. CT and fluorodeoxyglucose (FDG) PET/CT are both inaccurate in discriminating residual disease from pCR owing to the presence of wall thickening and/or radiation oesophagitis. The same is true for endoscopic ultrasonography (EUS), which has an accuracy of only 36 per cent for ypT determination.…”
Section: Introductionmentioning
confidence: 99%
“…To implement non‐surgical treatment for advanced oesophageal cancer it is critical to accurately identify pCR. CT and fluorodeoxyglucose (FDG) PET/CT are both inaccurate in discriminating residual disease from pCR owing to the presence of wall thickening and/or radiation oesophagitis. The same is true for endoscopic ultrasonography (EUS), which has an accuracy of only 36 per cent for ypT determination.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike preoperative chemotherapy, pCR can be highly anticipated after preoperative chemoradiation (9). A prospective cohort study with 138 EC patients (EAC 75%) showed that when complete metabolic response (cMR) was defined as maximal value of SUVmax of <4, only 27% patients who had cMR achieved pCR after chemoradiation (27). Elliot et al also reported similar result.…”
Section: Predicting Preoperative Chemoradiation Response By Pet-ctmentioning
confidence: 81%
“…Even if pathologic response could be accurately determined pre-operatively, and current data suggest this is not the case (8,9), surgery may still be an important factor in disease control. In fact, given the poor longterm outcomes, trials of further adjuvant treatment even in complete responders will probably also be required to augment response and further improve long-term survival.…”
Section: Nodal Involvement and Outcomementioning
confidence: 92%